REVIEW OF LOGISTICS SYSTEM FOR DEVELOPMENT OF LEADING COMMODITY AGROINDUSTRY TO SUPPORT SPECIAL ECONOMIC ZONES (SEZS) IN ACEH PROVINCE - Ramayana; Romano; Qhisthina Atikah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Agro-industry development is one of the priorities of Aceh's economic development which is based on increasing agricultural sector production as a source of raw materials for industry. The Aceh government has established the development of special economic zones as one of the strategic steps for economic development. This study aims to analyze the logistics system to support the development of the Aceh Special Economic Zone agroindustry in Lhokseumawe and its surroundings. This study uses a survey method by collecting data from various sources that will play a role in the development of agro-industry in this area. The input-output analysis model is used to see the role of each subsector in supporting agro-industry in the region. The research results show that the plantation sector is one of the providers of agro-industrial raw materials that still has the greatest opportunities with a raw material availability coefficient of between 111 and 239 percent. The main plantation commodities as raw materials are coconut, palm oil, coffee, and cocoa. The logistics index of raw material availability is 28 percent. Therefore, the Aceh Government prioritizes agro-industry based on the potential availability of agro-industry raw materials.